2019
DOI: 10.1371/journal.pone.0225281
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of prenatal screening and diagnostic strategies for Down syndrome: A microsimulation modeling analysis

Abstract: ObjectivesDown syndrome (DS) is the most frequently occurring fetal chromosomal abnormality and different prenatal screening strategies are used for determining risk of DS worldwide. New non-invasive prenatal testing (NIPT), which uses cell-free fetal DNA in maternal blood can provide benefits due to its higher sensitivity and specificity in comparison to conventional screening tests. This study aimed to assess the cost-effectiveness of using population-level NIPT in fetal aneuploidy screening for DS.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
13
0
3
Order By: Relevance
“…In 2019, Zhang et al [ 10 ] used a microsimulation decision-analytic model to conduct a sample survey of 45,605 pregnant women in British Columbia, Canada. They concluded that NIPT screening was more effective and more expensive, and NIPT at 200 USD or less was more cost-effective as a first-line screening strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Zhang et al [ 10 ] used a microsimulation decision-analytic model to conduct a sample survey of 45,605 pregnant women in British Columbia, Canada. They concluded that NIPT screening was more effective and more expensive, and NIPT at 200 USD or less was more cost-effective as a first-line screening strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Contingent screening, i.e., performing cfDNA only in those patients with high risk in the combined test, has shown to be a cost-effective way to enhance first-trimester combined test [5, 6, 8]; however, the difficulty lies in setting the cut-off threshold to consider the patient to be at increased risk to perform cfDNA test, since, depending on it, both the detection rate and the number of patients to be included in the program vary, and therefore the costs are also different. Gil et al [9] reported detection rates depending on the cut-off chosen for contingent screening: to achieve 100% detection of T21s, the cut-off point should be higher than 1:3,500.…”
Section: Discussionmentioning
confidence: 99%
“…This is the main reason why it has not been widely implemented to be used as universal first-trimester screening in national health programs, as this strategy has proven not to be cost effective [4]. In contrast, several studies have shown that contingent screening, i.e., the implementation of combined screening with cfDNA testing in at-risk populations, is a cost-effective strategy, and in fact, this is the trend that major health systems are focusing on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several articles about prenatal testing published over the last few years from China, the UK, Belgium, the US, Thailand, and Canada have included cost/benefit analysis as a justification for aneuploidy screening in their analyses and/or discussions [32][33][34][35][36][37][38].…”
Section: Preventing Genetic Disease: a Public Health Perspectivementioning
confidence: 99%